0181 Better Performance on The Psychomotor Vigilance Task is Associated with Longer Sleep Duration and Lower Self-reported Sleep Need in the Real World. (27th April 2018) - Flynn-Evans, E E; Arsintescu, L; Gregory, K; Mulligan, J; Nowinski, J; Feary, M
Abstract: Introduction: The psychomotor vigilance task (PVT) is sensitive measure of performance impairment arising from sleep loss and circadian misalignment. Some individuals maintain stable, good PVT performance during sleep restriction. It is unclear whether such individuals need less sleep or whether they are more resilient to the effects of sleep loss. We aimed to characterize the relationship between sleep duration and perceived sleep need with PVT performance under real-world conditions. Methods: We collected actigraphy (MotionWatch-8, CamNtech), sleep logs, and the PVT (3–10 times/day) from airline pilots over a 34-day fixed work schedule that began with a baseline (mid-morning start) and then varied between early and late shifts. We split the participants into quartiles by mean baseline PVT and calculated sleep duration, self-reported sleep need, and percentage of sleep obtained relative to perceived need. We used ANOVA to compare sleep outcomes between quartiles. Results: Thirty-seven participants completed the study (3F). Mean PVT scores over the entire study varied according to the baseline quartile split (quartile 1 [Q1]=229.1 ms ±84.9 SD; Q2=245.2 ms ±79.9; Q3=267.8 ms ±65.2; Q4=331.9 ms ±146.2) and remained stable irrespective of work schedule (e.g. Q1 performed best throughout). Actigraphy-derived sleep duration was significantly shorter among those in Q3 (6.4 h ±1.4; p=0.01) and Q4 (6.4 ± 1.5; p=0.01) compared to Q1 (6.8 h ±1.3). Participants in Q1 reported needing less sleep (7.7 h ± 0.7), but obtained a higher percentage of their self-reported sleep need (90%) on average compared to those in the other quartile categories (Q2=7.9 h ±0.6, 86%; Q3=8.0 h ±0.8, 81%; Q4=8.1 h ±0.7, 79%). Conclusion: We found that participants with the best PVT performance reported needing less sleep, but obtained more sleep on average than those in the poorer performing quartiles. Our findings confirm that longer sleep duration is associated with better PVT performance and suggest that sleep need may differ between individuals who are defined resilient and vulnerable according to the PVT. Support (If Any): NASA Airspace Operations and Safety Program.